Factors Influencing Financial Management of Village Fund Allocation: Study in Lubai Ulu District - Periansya, Periansya; Muamar, M.; Aryani, Yuli Antina (International Journal of Finance Research, 2023)
This research examines the impact of accountability, openness, and involvement on the financial management of village budget allocations in the Muara Enim district's Lubai ulu subdistrict. The sample included nine members of the village consultative committee from eleven communities within the subdistrict of Lubai Ulu. This study was conducted to assess how public accountability, transparency, and participation affect the administration of village budget allocations in the Muara Enim subdistrict of Lubai Ulu. The sample for this research consisted of 99 respondents from 11 villages in the Lubai ulu subdistrict. Respondents were chosen based on their direct involvement in reporting, decision-making, accountability, and administration in the financial management of local budget allocations. The result of this research was found accountability, transparency transparency, and participation partially have a positive and significant effect on the management of fund village allocations